In vitro induction of triploid roots and shoots from mature endosperm of Jatropha pandureafolia - Srivastava, P.S.
The mature endosperm of J. panduraefolia proliferated profusely on modified White's medium + 2,4-D + kinetin + YE. The tissue thus obtained grew compact upon continuous subculture and differentiated vascular cells. When callus pieces were transferred to WB + NAA + kinetin + CH, shoot buds and roots differentiated all round the callus. On WB + CH or WB + an auxin, only roots differentiated and on WB + kinetin, only shoots differentiated. In some cultures roots and shoots differentiated from the same callus. Anatomy of the in vitro-differentiated roots and shoots was comparable to in vivo Structures. Cytological preparations of Il-month-old callus showed polyploid cells and chromosomal abnormalities. My results indicate that mature endosperm can also differentiate into triploid organs.